2021
DOI: 10.1371/journal.pntd.0009273
|View full text |Cite|
|
Sign up to set email alerts
|

Laboratory demonstration of the vertical transmission of Rift Valley fever virus by Culex tarsalis mosquitoes

Abstract: Rift Valley fever virus (RVFV) is a mosquito-transmitted virus with proven ability to emerge into naïve geographic areas. Limited field evidence suggests that RVFV is transmitted vertically from parent mosquito to offspring, but until now this mechanism has not been confirmed in the laboratory. Furthermore, this transmission mechanism has allowed for the prediction of RVFV epizootics based on rainfall patterns collected from satellite information. However, in spite of the relevance to the initiation of epizoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Our results showed that, on average, RVF has the ability to remain endemic on the Comoros archipelago provided that the climate conditions remain favourable to support transmission. Within our framework, implicit persistence mechanisms can be ascribed to alternate wildlife hosts 36 , irregular introductions of infected hosts through trade 15 , or maintenance of the virus in local mosquito populations via transovarial transmission 37 , 38 . Serological surveys in potential wildlife hosts, imported animals and mosquito vectors would enable the routes for RVF persistence to be more precisely assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that, on average, RVF has the ability to remain endemic on the Comoros archipelago provided that the climate conditions remain favourable to support transmission. Within our framework, implicit persistence mechanisms can be ascribed to alternate wildlife hosts 36 , irregular introductions of infected hosts through trade 15 , or maintenance of the virus in local mosquito populations via transovarial transmission 37 , 38 . Serological surveys in potential wildlife hosts, imported animals and mosquito vectors would enable the routes for RVF persistence to be more precisely assessed.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti (Crabtree et al, 2012;Kading et al, 2014), 58 -95% for Cx. tarsalis (Bergren, Borland, Hartman, & Kading, 2021;Turell, Wilson, & Bennett, 2010) with midgut titers of over 6 log 10 PFU in actively infected Cx. tarsalis (Bergren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…tarsalis (Bergren, Borland, Hartman, & Kading, 2021;Turell, Wilson, & Bennett, 2010) with midgut titers of over 6 log 10 PFU in actively infected Cx. tarsalis (Bergren et al, 2021). Similarly, up to 100% infection occurred MP-12 infected Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of vertical transmission within insect vector species other than floodwater Aedes spp. mosquitoes [164] indicates the existence of multiple pathways for local RVFV persistence in different ecosystems during time periods that are in between recognized outbreaks. An additional non-vector route of RVFV transmission to humans, i.e., maternal-fetal transmission, has also been identified recently [165][166][167], and it has been established that RVFV can be an abortifacient in humans [168].…”
Section: Evidence Of Vector Presence and Competence For Interepidemic Rvfvmentioning
confidence: 99%